2021
DOI: 10.3390/ma14227067
|View full text |Cite
|
Sign up to set email alerts
|

Application of Modern Research Methods for the Physicochemical Characterization of Ion Exchangers

Abstract: Ion exchange technique as the reversible exchange of ions between the substrate and the surrounding medium can be an effective way of removing traces of ion impurities from the waters and wastewaters and obtaining a product of ultrapure quality. Therefore, it can be used in analytical chemistry, hydrometallurgy, purification and separation of metal ions, radioisotopes and organic compounds, and it also finds great application in water treatment and pollution control. In the presented paper, the new trends for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…3a-c), it was observed that quaternary amine sorbents (A500Plus, MP500, K6362, and IRA904) did not show affinity toward any of the target elements of interest for the project (removals <10%) and that only appreciable Ga and Ge sorption (25-30%) was achieved by A500Plus with bittern 1 and IRA904 with bittern 3 (25-35%). This would be in accordance with the explanation of Yi-Gong Chen et al (2021), 64 where it is said that strong basic anion exchangers with quaternary ammonium groups could have good kinetics and short rinses but, in contrast, not a very high exchange efficiency. Among tertiary amine sorbents, IRA94 did not show affinity toward any element, but A100 was able to sorb around 67%, 62%, and 52% Co for bitterns 1, 2, and 3, respectively.…”
Section: Speciation Of Trace Elements In Bitternssupporting
confidence: 91%
See 2 more Smart Citations
“…3a-c), it was observed that quaternary amine sorbents (A500Plus, MP500, K6362, and IRA904) did not show affinity toward any of the target elements of interest for the project (removals <10%) and that only appreciable Ga and Ge sorption (25-30%) was achieved by A500Plus with bittern 1 and IRA904 with bittern 3 (25-35%). This would be in accordance with the explanation of Yi-Gong Chen et al (2021), 64 where it is said that strong basic anion exchangers with quaternary ammonium groups could have good kinetics and short rinses but, in contrast, not a very high exchange efficiency. Among tertiary amine sorbents, IRA94 did not show affinity toward any element, but A100 was able to sorb around 67%, 62%, and 52% Co for bitterns 1, 2, and 3, respectively.…”
Section: Speciation Of Trace Elements In Bitternssupporting
confidence: 91%
“…K3 and K5 belong to fibrous sorbents with carboxylic acid functional groups but with amines on their structure. These kind of fibrous ion exchangers, due to their mechanical strength and flexibility, 70 are applied for air purification, 64 but they could also be used to extract several metals from water. 71 Independent of which bittern was tested (Fig.…”
Section: Speciation Of Trace Elements In Bitternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorbents bearing various chelating ligands were prepared by two main strategies: (i) post-functionalization of commercially available [ 12 , 13 , 14 , 15 , 16 ] or homemade [ 12 , 17 , 18 , 19 , 20 ] cross-linked copolymers; (ii) “bottom-up” design of specialized materials by the free radical polymerization of monomers endowed with adequate pre-existing heteroatomic moieties, such as –COOH, –OH, –SH, –NH 2 , =NH, –N=, –SO 3 H, and –PO 3 H, in the presence of a cross-linker [ 18 , 20 , 21 ], or by the condensation of monomers containing a high density of reactive functional groups [ 12 , 22 ]. Even so, all the sorbents described above have weak selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the years, various pump and treat physicochemical technologies have been employed to remediate Cr(VI) polluted soil and groundwater (ion exchange, chemical precipitation, adsorption, membrane filtration, etc.) [5][6][7][8]. However, these technologies present certain disadvantages, such as secondary pollution, high operational and maintenance cost, and low effectiveness [9,10].…”
Section: Introductionmentioning
confidence: 99%